Prevention of obstetric complications against the background of retrochoric hematoma in the i trimester of pregnancy - Т. Г. Романенко; О. М. Суліменко (Publishing House TRILIST, 2018)
In modern obstetrical and gynecological practice, the problem of miscarriage, one of the manifestations of which is the retrochoric hematoma, does not lose its relevance. Despite numerous studies of the etiology and pathogenesis of this problem, there are still many questions that need answers. The purpose of this systematic review was to highlight the problem of retrochoric hematomas, the etiological features of their occurrence and the importance of treatment in order to avoid the development of further complications, the preservation and prolongation of pregnancy. The features of diagnostics and subsequent therapy with the main pathogenetically grounded drug, micronized progesterone, are considered, which provides early support for pregnancy and a reduction in the frequency of obstetric and perinatal complications that combine into large obstetrical syndromes. Analyzed data from modern world studies suggest that it is progestins (micronized progesterone) that should be the drug of choice in the treatment of miscarriage, which occurs against the background of retrochorial hematoma. The conclusion of the expert group of ESHRE on special issues of early pregnancy is: in women with bleeding in early pregnancy and the formation of retrochoric and retrocopental hematomas the risk of premature birth, the development of fetal growth retardation syndrome, placental abruption in the 2nd and 3rd trimesters is increased. In order to prevent preterm delivery experts recommend prolongation of therapy with micronized progesterone (200 mg per day intravaginally from early pregnancy). In the diagnostics of retrochoric hematoma the tactics of management should be based on the therapy of preserving pregnancy and preventing its further complications. The high efficacy of micronized progesterone Utrozhestan and haemostatic therapy in the treatment of abortion complicated by retrochoric hematoma allows prolonging pregnancy and achieving favorable perinatal outcomes. The absence of side effects and good tolerance extend the possibilities of using Utrozhestan by women with retrochoric hematoma in case of a threat of termination of pregnancy.